Adult limb fractures - Siddiqui, Ahmed Mujtaba (GMM, 2002)
This pocketbook uses specially generated line diagrams throughout to illustrate all of the major classification schemes currently used to identify fractures of the extremities. It is an essential quick reference for the trainee orthopaedic surgeon, both in the hospital environment and as a revision aid for the orthopaedic component of the MRCS examination, but it will also prove valuable to all personnel in the casualty environment, who need to be able to interpret and understand the different types of fracture and how different injuries affect patient management and subsequent clinical decision-making.